2007
DOI: 10.1007/s10750-007-9046-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of rotifers in a large lowland river, the Elbe, Germany: How important are retentive shoreline habitats for the plankton community?

Abstract: The longitudinal dynamics of Rotifers in the Potamal region of the River Elbe between Dresden, km 46, and Geesthacht, km 583, was investigated on a Lagrangian survey in 2000 which included transversal sampling (left bank, main channel, right bank) and sampling of five major tributaries and backwaters to evaluate lateral impacts on the zooplankton community. A simple model of longitudinal development for the dominant species Trichocerca pusilla was calculated, based on the results of an in situ incubation in Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
2
27
1
Order By: Relevance
“…These water bodies changed the environmental conditions with regard to significantly higher, orthophosphates, suspended organic matter and Chl a concentrations. According to the findings of other authors (Zimmermann-Timm et al, 2007), lentic parts enriched downstream lotic stretch in running waters with nutrients and organic matter, especially where lentic stretches prevailed over lotic, as in the Jankovac hydrosystem alike Plitvice lakes, Croatia (Sˇpoljar et al, 2007a, b).…”
Section: Environmental Conditionsmentioning
confidence: 85%
“…These water bodies changed the environmental conditions with regard to significantly higher, orthophosphates, suspended organic matter and Chl a concentrations. According to the findings of other authors (Zimmermann-Timm et al, 2007), lentic parts enriched downstream lotic stretch in running waters with nutrients and organic matter, especially where lentic stretches prevailed over lotic, as in the Jankovac hydrosystem alike Plitvice lakes, Croatia (Sˇpoljar et al, 2007a, b).…”
Section: Environmental Conditionsmentioning
confidence: 85%
“…Similar domination of rotifers was observed in several rivers including the Elbe (Zimmermann-Timm et al 2007), the Danube (Reckendorfer et al 1999), the Loire (Lair & Reyes-Marchant 1997), the Rhine (Friedrich & Pohlmann 2009), the Po (Rossetti et al 2009) and the Darling (Shiel 1985). It has been suggested that the apparent dominance of rotifers in rivers maybe due to their relatively short generation times compared to the larger crustacean zooplankton (van Dijk & van Zanten 1995;Lair 2006).…”
Section: Discussionmentioning
confidence: 58%
“…Water residence time increases with the increasing river length and there is often a tendency for plankton to be more abundant downstream. Generally these downstream increases have been associated with the increases of time available for plankton to develop (Viroux 1999;Zimmermann-Timm et al 2007). So we can say that the "Age of Water" (Baranyi et al 2002) is very important for zooplankton development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rivers, zooplankton assemblage is often dominated by rotifers, bosminids and juvenile copepods throughout the year, with a negligible occurrence of large-body cladocerans and calanoid populations (Kobayashi, 1997;Viroux, 1997;Welker and Walz, 1998;Sˇpoljar et al, 2007Sˇpoljar et al, , 2012aSˇpoljar et al, , 2012bZimmermann-Timm et al, 2007). Rotifers, often the main component in freshwater ecosystems, play a key role in the pelagic food chain; they are a fundamental link between phytoplankton and secondary consumers, since they act as vector in the matter and energy transfer from bacteria and small detrital particles, not consumed by other planktonic organisms at higher food chain levels (Conde et al, 2004).…”
Section: Introductionmentioning
confidence: 99%